Implementing research-based climate action for better adaptation - Kinyua, Ivy Wambui (Nation Media Group, 2022)
Today’s global challenges of poverty, malnutrition, climate change, land degradation, and biodiversity loss call for new research, solutions, innovations, and stronger partnerships that can deliver a higher impact. The Alliance of Bioversity International and CIAT, building on its complementary mandates and extensive collaborations, delivers research-based solutions that harness agricultural biodiversity and sustainably transform food systems to improve lives. The Alliance works with local, national, and multinational partners across Africa, Asia, Latin America, and the Caribbean, and with public and private sector players, to generate evidence and mainstream innovations in largescale programs to create food systems and landscapes that sustain the planet, drive prosperity, and nourish people. The Alliance is part of CGIAR, the world’s largest agricultural research and innovation partnership for a food-secure future, dedicated to reducing poverty, enhancing food and nutrition security, and improving natural resources.